Desempenho produtivo e qualidade de ovos de galinhas poedeiras em segundo ciclo de postura alimentadas com minerais orgânicos - Carvalho, Letícia Souza Silva (2012)
CHAPTER 2: The goal of this research was to evaluate the performance of laying hens in second laying cycle, fed with minerals from organic source. The control treatment consisted of diets with inorganic mineral premix, and other treatments consisted of organic copper, iron, manganese and zinc organics in levels of 100%, 90%, 80% and 70% of inorganic minerals levels. The specific gravity and percentage of body checked eggs did not suffer influence from treatments. The egg weight had a decrease when birds were fed with organic minerals. The egg production percentage was higher when 100% of the organic minerals were included, while the feed conversion ratio better on treatments with addition of 100% and 90% organic minerals. Other addition levels provided percentage of and feed conversion ratio statistically equal to the control. Total replacement of inorganic trace minerals for equal levels of organic minerals in the diet of laying hens provided improvement in the performance. When replacement resulted in up 70% of that inclusion of inorganic minerals were maintenance of performance parameters. CHAPTER 3: The aim of this study was to evaluate the influence of the copper, iron, manganese and zinc minerals in organic form, associated to the internal and external quality parameters on hen eggs in their second production cycle. Such treatments consisted of the total replacement of this trace minerals in their inorganic form by the addition of organic mineral at levels of 100%, 90%, 80% and 70% commonly used in commercial farms. Physical and chemical analyses were performed to evaluate quality of eggs. Percentage of albumen, yolk and eggshell did not suffer influence from treatments. Percentage of protein decreased with the use of organic minerals while the mineral matter increased. The eggshell quality parameters had an improve with the addition of organic minerals on the diet of laying hens. The inclusion of minerals from organic source to laying hens diet in their second production cycle provided a highest percentage of mineral matter, in albumen and yolk, and better eggshell quality.